A flexible SERS-active film for studying the effect of non-metallic nanostructures on Raman enhancement. Issue 35 (3rd September 2018) - Wang, Guilin; Yi, Ronghua; Zhai, Xueting; Bian, Renji; Gao, Yongqian; Cai, Dongyu; Liu, Juqing; Huang, Xiao; Lu, Gang; Li, Hai; Huang, Wei
Abstract : A flexible SERS-active film was attached onto nanostructured non-metal surfaces to investigate the effect of non-metallic nanostructures on Raman enhancement. Abstract : Since the discovery of surface enhanced Raman scattering (SERS), the choice of SERS-active materials has been limited mainly to metals, especially gold and silver in the visible spectrum. Although non-metals can also be SERS-active by forming nanostructures or composite structures with SERS-active materials, the mechanism behind it is still unclear and there is no perfect technique to study it. In this work, by constructing a SERS structure on a flexible polydimethylsiloxane film, we provide a way to study the effect of non-metallic nanostructures on Raman enhancement by attaching the above film onto flat and nanostructured surfaces. It was found that a nanoporous silicon surface contributes to an additional, up to five times, Raman enhancement. The pore depth and pore size also influence the observed Raman enhancement. These findings will help us not only to understand the mechanism of SERS involving non-metallic nanostructures, but also to design more efficient SERS structures for various applications.